Patient dose in angiographic interventional procedures: A multicentre study in Italy. (August 2019) - Isoardi, Paola; D'Ercole, Loredana; Cavallari, Monica; Gianusso, Laura; Pini, Silvia; Giordano, Carlo; Angelini, Lidia; Colombo, Paola Enrica; Canne, Stefania Delle; Vecchio, Antonella Del; Di Liberto, Riccardo; Farnedi, Simona; et al.
Highlights: Attempt to obtained reference levels useful to optimize work modality. Our reference levels are comparable with ISTISAN DRL (17/33) and literature data. Optimization is required for some centres. Abstract: Purpose: The Council Directive 2013/59/EURATOM considers interventional radiology to be a special practice involving high doses of radiation and requiring strict monitoring to ensure the best quality assurance programs. This work reports the early experience of managing dose data from patients undergoing angiography in a multicentre study. Materials and methods: The study was based on a survey of about 15, 200 sample procedures performed in 21 Italian hospitals centres involved on a voluntary basis. The survey concerned the collection of data related to different interventional radiology procedures: interventional cardiology, radiology, neuroradiology, vascular surgery, urology, endoscopy and pain therapy from a C-Arm and fixed units. The analysis included 11 types of procedures and for each procedure, air-kerma, kerma-area product and fluoroscopy time were collected. Results: The duration and dose values of fluoroscopic exposure for each procedure is strongly dependent on individual clinical circumstances including the complexity of the procedure; the observed distribution of patient doses was very wide, even for a specified protocol. The median values of the parameters were compared with the diagnostic reference levels (DRL) proposed for some procedures in Italy (ISTISAN) or internationally. This work proposes local DRL values for three procedures. Conclusion: This first data collection serves to take stock of the situation on patient's dosimetry in several sectors and is the starting point for obtaining and updating DRL recalling that these levels are dependent on experience and technology available.